Saberes ancestrales y medicina tradicional en EDAS e IRAS. Centro de salud Cachisagua. Enero - abril 2023 - Fernandez Mullo, Cinthia Liseth (2023)
Traditional medicine, rich in ancestral knowledge, continues to play a vital role in healthcare in various communities. At the Cachisagua Health Center, the prevalence of traditional practices and beliefs in the treatment of acute diarrheal diseases (ADD) and acute respiratory infections (ARI) in children under five years old was observed. The study aimed to identify the cultural practices and beliefs applied by the mothers of children under 5 years old for the treatment of ADD and ARI, which are attended to at the Cachisagua Health Center between January and April 2023. A descriptive quantitative approach was adopted. The study population consisted of 81 mothers of children who attended the Cachisagua Health Center between January and April of 2023. A structured survey was used to collect data on cultural practices and beliefs, as well as on the plants and herbs used in traditional medicine. It was identified that, although the mothers attend the health center, they trust in traditional medicine. For ADD, medicinal teas and plant poultices predominate. For ARI, infusions of linden, mint, rosemary, among others, are used. 49.4% of mothers use teas with onion root and oregano for ADD, and 53.1% use infusions such as linden and mint for ARI. In conclusion, mothers, despite access to modern medicine, significantly lean towards traditional therapies. This coexistence of paradigms underlines the diversity of the health approach in Cachisagua. It is imperative to respect and value traditional knowledge, integrating it with modern knowledge, to provide holistic and culturally sensitive medical care. The designed guide serves as a bridge between these two worlds, merging the best of both to benefit the community Keywords: ancestral knowledge, traditional medicine, acute diarrheal diseases, acute respiratory infections.